Albanian Domestic Law and Case Law versus New York Convention, Regarding the Recognition of Foreign Arbitral Award: Some Problematic Issues - Spahiu, Artan (Insights into Economics and Management Vol. 9, 2021)
The growing expansion of international trade and investment is associated with the tendency to transform the international commercial arbitration into a mechanism increasingly used to settle disputes arising from these relationships. Some states are not very attracted by international arbitration, what is easily evidenced by the low level of modernization of the relevant legislation and the lack of consolidation of judicial practice. Albania is a similar country. This article aims to discuss, in a comparative light, some important issues in Albanian legal framework and even in the Albanian case law, compared to the New York Convention provisions, concerning the foreign or domestic status of an arbitral award and obstacles for its recognition and enforcement in the Republic of Albania. In this way, some problematic issues addressed by the domestic legal framework are to be presented as well as the necessity for eventual changes. Adoption and implementation of legal instruments, which provide contemporary improvements of arbitration institute, in accordance with the international legal framework, will be a good service to the integration process of the Albanian economy.